G124(P) Junior doctor perspectives on exception reporting – a snapshot of current opinion and predicted themes. (12th March 2018) - Manning, GLP; Das, D; Yeop, I; Hassell, J; Rawlinson, E
Abstract : Aims: Following divisive contract negotiations, with significant pressure on the NHS, and an inflexible postgraduate training system, there is growing concern for junior doctor (JD) morale and engagement. The new JD contract introduces a powerful tool for positive change – the Exception Report (ER). Initial rates of ER have been low, with concerns of JD disillusionment and potential for dis-engagement if responses to ER are perceived as insensitive. We aimed to identify current JD thoughts, ideas and feelings on ER at a specialist paediatric hospital. Methods: A focus group was held to characterise current JD opinion on ER. The group was advertised primarily to Junior Doctor Forum (JDF) members, with JDF members asked to invite their JD colleagues. Eight JDs attended a structured focus group. Opinions and ideas were sought on ER triggers and root-causes, and on potential solutions, as well as current feelings on ER and supervisor approaches to ER that were anticipated to be conciliatory or inflammatory. Findings were presented as mind-maps to the JDF to review completeness and validity. Results: Pervasive themes of clinical workload, doctor-specific admin, staff mix and resultant pressure on educational opportunities arose, along with a recognition that these issues transcend staffing groups. ER was strongly felt to be part of constructive departmental system/structural review, rather than a reflection on the reporter. Themes from the focus group are supported by currently submitted ERs. Conclusion: ER should be considered a symptom of a just departmental culture. They should be used positively to identify system issues, with the baseline assumption that the trainee is not at fault. Financial compensation and time-off-in-lieu (TOIL) are recognised as important, fair, and necessary for safe and sustainable practice, however, recognition of effort, work and personal sacrifice are considered indispensable.